2017
DOI: 10.5039/agraria.v12i3a5459
|View full text |Cite
|
Sign up to set email alerts
|

Fitotoxidez de mesotriona em milho inoculado com Azospirillum brasilense associado a adubação nitrogenada

Abstract: RESUMOEste estudo objetivou avaliar a fitotoxidez do herbicida mesotriona no desenvolvimento inicial do milho inoculado com Azospirillum brasilense, associado à adubação nitrogenada. O delineamento utilizado foi o de blocos casualizados, em esquema fatorial 2x3, representado por milho com e sem aplicação do mesotriona (192 g ha) e os tratamentos: 1-inoculação das sementes com A. brasilense; 2-aplicação em cobertura de 140 kg ha -1 de N; e 3-A. brasilense + 140 kg ha -1 de N em cobertura aplicado aos 26 dias ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…When considering the supply caused by the plant growth promotion bacteria A. brasilense, it is observed that the results of the present study are inconclusive in relation to the capacity to raise the dry mass of plants. These results may have occurred by the cultivation condition, which was in pots, where the increases in the root system are limited by its exploration area, as that no hydric limitation occurred, condition where the use of A. brasilense brings increases to tropical pastures (Bulegon, Inagaki, Moratelli, Costa, & Guimarães, 2017). It is worth mentioning that the absence of conclusive results in the present study, provided by the inoculation with A. brasilense, may be associated with the genetic characteristics of the used material, where the study was conducted beyond the intervals between inoculation and evaluation (Alcântara, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…When considering the supply caused by the plant growth promotion bacteria A. brasilense, it is observed that the results of the present study are inconclusive in relation to the capacity to raise the dry mass of plants. These results may have occurred by the cultivation condition, which was in pots, where the increases in the root system are limited by its exploration area, as that no hydric limitation occurred, condition where the use of A. brasilense brings increases to tropical pastures (Bulegon, Inagaki, Moratelli, Costa, & Guimarães, 2017). It is worth mentioning that the absence of conclusive results in the present study, provided by the inoculation with A. brasilense, may be associated with the genetic characteristics of the used material, where the study was conducted beyond the intervals between inoculation and evaluation (Alcântara, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, although mesotrione is a selective herbicide for use in maize, it can cause up to 35% intoxication (Bulegon et al, 2017), which is characterized by white spots in the new leaves of maize plants. Such spots become chlorotic and there is subsequent necrosis of the leaf tissue in the most extreme conditions (Barchanska et al, 2014), thereby interfering with crop plant metabolism (O'Sullivan et al, 2002;Ogliari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%